2019
DOI: 10.3892/etm.2019.7377
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of leptin against cerebral ischemia/reperfusion injury (Review)

Abstract: In recent years, the use of thrombolytic therapy for treating ischemia/reperfusion injury has resulted in damage to the self-regulatory mechanisms of the brain. This is due to the increased production of free radicals, excitatory amino acids and pro-inflammatory cytokines causing secondary damage to the brain. Simple thrombolytic therapy has not been the best approach for treating ischemia/reperfusion injury. Excessive perfusion leads to failure of the body's self-regulatory functions, which in turn increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 93 publications
2
31
0
Order By: Relevance
“…Meanwhile, it also suppresses erastin-induced ferroptosis [ 178 ]. Leptin is an adipocyte-derived hormone that acts as inhibiting glutamate release in the hippocampal CA3 field [ 179 ], which attenuates ferroptosis induced by glutamate excitotoxicity [ 180 ], increases cerebral blood flow in hypoperfused rat brains, protects neurologic function, and reduces infarct size [ 181 , 182 ]. However, a research found that the leptin level is high in patients and mice after acute ischemic stroke [ 183 ].…”
Section: Pharmacotherapies For Ischemic Stroke Targeting Ferroptosis and Necroptosismentioning
confidence: 99%
“…Meanwhile, it also suppresses erastin-induced ferroptosis [ 178 ]. Leptin is an adipocyte-derived hormone that acts as inhibiting glutamate release in the hippocampal CA3 field [ 179 ], which attenuates ferroptosis induced by glutamate excitotoxicity [ 180 ], increases cerebral blood flow in hypoperfused rat brains, protects neurologic function, and reduces infarct size [ 181 , 182 ]. However, a research found that the leptin level is high in patients and mice after acute ischemic stroke [ 183 ].…”
Section: Pharmacotherapies For Ischemic Stroke Targeting Ferroptosis and Necroptosismentioning
confidence: 99%
“…The neuroprotective effects of leptin extend to various models of CNS-driven disease including models of ischaemia [ 62 , 63 , 64 ]. Indeed, after transient periods of ischaemia, treatment with leptin is reported to reduce the size of cerebral infarcts and degree of brain oedema [ 65 ].…”
Section: Leptin and The Ageing Brainmentioning
confidence: 99%
“…Corydalis yanhusuo can promote coronary artery dilation, protect against arrhythmia and myocardial and cerebral ischemiareperfusion injury, and alleviate myocardial infarction. 1,102 Tetrahydropalmatine can decrease norepinephrine and catecholamine in rat blood vessels and peripheral tissues, respectively, which may subsequently contribute to reduced heart rate and blood pressure. 60,61 This compound can also lower blood pressure by blocking voltage-dependent calcium channels.…”
Section: Effects On the Cardio-cerebrovascular Systemmentioning
confidence: 99%